Measurement of reflection from various types of coating materials [compact disc] - 259343 Mohd. Yusri Yusop (Skudai : Universiti Teknologi Malaysia, 2004)
Project Paper (Bachelor of Science (Industrial Physics)) - Universiti Teknologi Malaysia, 2004